Building Bridges Through Collaboration and Consensus: Expanding Awareness and Use of Peer Support and Peer Support Communities Among People With Diabetes, Caregivers, and Health Care Providers. (March 2019) - Warshaw, Hope; Edelman, David
Diabetes, regardless of type, is a complex disease. Successful management to achieve both short- and long-term health goals and outcomes is highly dependent on learning, mastery, and regular implementation and execution of self-care behaviors. The importance of a positive mental outlook and minimization of psychosocial barriers to care is increasingly identified as important in managing the whole person with diabetes and, as appropriate, the caregivers. Ongoing support from HCP and increasingly ongoing support from peers are critical elements of quality diabetes care. With the availability of virtually accessible technologies for social media and networking, the volume of peer support among people with diabetes and their caregivers has increased exponentially and will likely continue to do so. With the value of ongoing peer support recognized as an important element in diabetes health, a growing number of peer support communities and increasing engagement in these communities among some diabetes educators, the American Association of Diabetes Educators (AADE) embarked on an initiative to more formally work with diabetes peer support communities and their leaders. To initiate this effort AADE held and supported a consensus meeting in 2017. This article reviews the history and goals of this effort and details the meeting outcomes. It also discusses the collaborations completed since the initial meeting along with plans for the near future. This collaboration is unique and presents a model for similar endeavors in diabetes or other chronic diseases.